Self-pumping transpiration cooling with phase change for sintered porous plates. (August 2019) - Huang, Gan; Liao, Zhiyuan; Xu, Ruina; Zhu, Yinhai; Jiang, Pei-Xue
Highlights: Self-pumping transpiration cooling was tested investigated in a wind tunnel. The system was stable and temperature distributions were homogeneously. This cooling system became more stable with smaller pores. Abstract: This study experimentally investigated self-pumping transpiration cooling in a hot wind tunnel. The coolant (liquid water) automatically and continuously flowed from the water tank to the heated porous surface without the use of any pump and then evaporated on the porous surface, thereby dissipating a large amount of heat. The self-pumping cooling system was stable and the temperature distributions were homogeneously maintained at approximately 373 K with a cooling efficiency of 86%. The entrainment ratio was approximately 0.4 in the mainstream conditions of this research. The unsteady and inhomogeneous problems in traditional transpiration cooling systems were successfully solved by this self-pumping transpiration cooling system. The particle diameter of the sintered porous plate had a slight influence on the coolant mass flow rate. However, the cooling system broke down when the particle diameter was too large to provide a sufficient capillary force. The coolant mass flow rate exhibited a rapid and automatic response to changes in the mainstream velocity and temperature, while the porous surface temperature remained constant. A Mathematical model was built to predict the coolant mass flow rate of this self-pumping transpiration cooling system coupled with the mainstream and the feasible particle size.